Globalization in prehistory contact, exchange, and the "people without history" - Boivin, Nicole 1970-; Frachetti, Michael D. (New York, NY Cambridge University Press, 2018)
"Globalization in Prehistory challenges traditional historical and archaeological discourse about the drivers of social and cultural connectivity in the ancient world. It presents archaeological case studies of emerging globalization from around the word, from the Mesolithic period, through the Bronze and Iron Ages, to more recent historical times. The volume focuses on those societies and communities that history has bypassed - nomads, pastoralists, fishers, foragers, pirates and traders, among others. It aims for a more complex understanding of the webs of connectivity that shaped communities living outside and beyond the urban, agrarian states that are the mainstay of books and courses on ancient civilizations and trade. Written by a team of international experts, the rich and variable case studies demonstrate the important role played by societies that were mobile and dispersed in the making of a more connected world long before the modern era"--Provided by publisher.
Introduction. Archaeology and people without history Nicole Boivin and Michael D. Frachetti--1. What's the point? Globalization and the emergence of ceramic-using hunter-gatherers in Northern Eurasia Peter Hommel--2. Globalizing interactions in the Arabian neolithic and the 'Ubaid Robert Carter--3. Domestic dispersal, human agency and the connectivity in Island Southeast Asia during the Holocene Tim Denham--4. Bronze Age participation in a 'global' ecumene: mortuary practice and ideology across Inner Asia Michael D. Frachetti and Elissa Bullion--5. Prehistoric globalizing processes in the Tao River Valley, Gansu, China? Yitzchak Jaffe and Rowan Flad--6. Global networks and local agents in the Iron Age Eurasian steppe Ursula Brosseder and Bryan K. Miller--7. Nomads and caravan trade in the Syrian Desert Eivind Heldaas Seland--8. Invisible agents of Eastern trade: foregrounding Island Southeast Asian agency in pre-modern globalization Tim Hoogervorst and Nicole Boivin--9. From rural collectables to global commodities: copper from Oman and obsidian from Ethiopia Ioana A. Dimitru and Michael J. Harrower--10. The Tsodilo Hills and the Indian Ocean: small-scale wealth and emergent power in eighth-eleventh century Central-Southern Africa Edwin N. Wilsen--11. Christians and spices: hidden foundations and misrecognitions in European colonial expansion to South Asia Kathleen D. Morrison--12. Subsistence middlemen traders and pre-colonial globalization in Melanesia Ian Lilley.
Includes bibliographical references and index.
Keywords: Prehistoric commerce; Culture diffusion; Local exchange trading systems